Isolation of 4000 SARS-CoV-2 shows that contagiousness is associated with viral load, not vaccine or symptomatic status. Issue 1 (1st January 2021) - Boschi, Celine; Aherfi, Sarah; Houhamdi, Linda; Colson, Philippe; Raoult, Didier; Scola, Bernard La
ABSTRACT: Culture inoculation of 6722 nasopharyngeal samples since February 2020 allowed isolation of 3637 SARS-CoV-2 and confirmed that isolation rate is correlated to viral load, regardless symptomatology or vaccination status. Moreover, the delta variant is associated with higher viral loads and therefore higher rates of viral isolation, explaining its greater contagiousness.